2005
DOI: 10.1246/cl.2006.100
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Dissociation of Carbohydrate Ligand Polycations from DNA Ternary Complexes

Abstract: Here, we have demonstrated that carbohydrate ligand polycations are pH-dependently dissociated from DNA polyion complexes. In response to pH, DNA ternary complexes have dissociated the ligand polycations, resulting in DNA binary complexes. Namely, the ternary complexes of DNA, a poly(L-histidine) modified with aminoethyl groups, PLH-NH 2 , and a poly(L-lysine) conjugated with lactose molecules, PLL-Lac, at pH 7.5 have dissociated the PLL-Lac polycations by the protonation of imidazole groups of PLH-NH 2 at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…The neutral or negatively charged nonviral gene carriers have poor ability to interact with the cell membrane. In this study, even without any targeting ligands, 20,21 efficient gene delivery was achieved. The total gene expression depended on the incubation time (Figure S-3, Supporting Information).…”
mentioning
confidence: 93%
“…The neutral or negatively charged nonviral gene carriers have poor ability to interact with the cell membrane. In this study, even without any targeting ligands, 20,21 efficient gene delivery was achieved. The total gene expression depended on the incubation time (Figure S-3, Supporting Information).…”
mentioning
confidence: 93%
“…We have already reported the concept that DNA ternary complexes dissociate ligand polycations in response to endosomal pH. , In this study, as shown in Figure , we examined the pH-dependent dissociation of PLL-Lac from the DNA ternary complexes with the PLL-Lac and the PVIm-Zn by agarose gel electrophoresis. It should be noted that free DNA was observed in spite of the mixing at a positive/negative ratio of 2 in case of PVIm-Zn/DNA binary complexes at pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…We have already reported pH-sensitive binary or ternary complexes containing imidazole groups for efficient gene delivery. , Especially, gene expression depends on our new concept that DNA ternary complexes dissociate carbohydrate ligand polycations in response to endosomal pH. , However, the charge ratio of polycation to DNA is relatively higher, that is, 5. Furthermore, we have proven that the pH-dependent chelation of Zn 2+ ions with the imidazole groups of poly(1-vinylimidazole) (PVIm) and that the zinc-chelated PVIm (PVIm-Zn) formed the DNA polyion complex via chelated Zn 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…The imidazole ring is involved in many physiological processes and therefore imidazole-containing systems have been investigated for a myriad of biological applications [5]. Poly(vinylimidazole) is a water-soluble polymer, which has been synthesized as poly(1-vinylimidazole) and poly(4-vinylimidazole) [6] by using different methods. The imidazole groups can be protonated at acidic pH values conferring cationic character to the polymer.…”
Section: Introductionmentioning
confidence: 99%